Surface Modification of Polycarbonate by Atmospheric Pressure Cold Argon/Air Plasma Jet - Baniya, H.B.; Shrestha, R.; Shrestha, A.; Shrestha, S.; Gurung, J.P.; Shrestha, A.K.; Subedi, D.P. (Kathmandu University Journal of Science, Engineering and Technology, 2014)
In this paper, atmospheric pressure plasma jet and its application for polymer surface modification is reported. Atmospheric pressure plasma jet sustained in Argon/Air mixture has been used to modify the surface properties of polycarbonate (PC). The surface properties of the untreated and plasma treated PC samples were characterized by contact angle measurement with water and glycerol. The contact angles were used to determine the surface energy and its polar and dispersion components. The effect of treatment time, frequency of the applied voltage, distance of the sample from the nozzle on the wettability of the sample was studied. It was found that the contact angle of water in untreated PC sample is 89° while it decreases to 35° after 5 minutes of treatment time. Moreover, it was found that, the best plasma treatment can be obtained with frequency 27 kHz and a distance of 1 cm between surface of samples (PC) and plasma jet's nozzle. Our result showed that atmospheric pressure non thermal plasma can be effectively used to enhance the surface wettability and surface energy of PC.